Ničnost pravnega posla zaradi nasprotovanja prisilnim predpisom - Juhart, Miha (Pravni letopis, 2011)
Nullity applies to strictest legal consequence of violation at conclusion of contract. In general rules of Law of Contracts the cause of nullity is found out with general clause of Article 86 of the Obligation Code. The contract is null (void), if its content opposes the constitution, strict rules and basic moral principles. Alongside the general clause we can find numerous provisions that especially determine legal consequence of nullity. The object is to eliminate any doubt about the legal nature of consequence of a violation. On the other hand we can also find some special provisions that enable the validity of the contract in spite of violation of some strict rules. Such institutes are especially the impact of the realization and the partial nullity. In last few years a number of public laws contain the special and categorical provision about the nullity of the contract. Categorical designation of nullity objects keeping the validity of contract. Author is critical to such legislative practice. In many cases the public interests concerning the violation could be reached by other legal consequences, especially with challenging the validity of contract.
Keywords: challenging the contract; corruption; delna ničnost; izpodbojnost; korupcija; neveljavnost; ničnost; nullity; obligacije; obligacijsko pravo; partial nullity; pogodbe; prisilni predpisi; strict rules; teorija o realizaciji; theory of realization